Fiber to improve the mechanical performance of concrete structural elements - Tamara Rodriguez, Joaquín Samuel (2021)
It is getting more frequent the deteriorated work rehab, the corrections of design flaws or poor constructive process. Because of this, it is required not only to rehabilitate but to rearrange the structures taking into consideration that that intervention have to fulfill the mechanic improvements. This research intents to make known the benefits that the reinforced polymer composite systems with carbon fiber give to improve the mechanical performance of structural concrete elements. The results of the resistance to the compression trials at 28 days of the unreinforced specimens was of 12 MPa, and with the incorporation of the reinforced polymer with carbon fiber (RPCF) at 100% it improves 2.67 times its resistance (32.04 MPa), while the reinforced specimens at 50%, improves 1.57 times its resistance (18.84 MPa). It can be concluded that the application of the RPCF, considerably increases the resistance to the compression and the concrete deformation, being a viable option as a reinforcement method; in addition, it was identified that the optimal treatment on the structural surface for the application of the RPCF is the sandblasting and punched because it got a compression resistance and outbreak of 55 and 2.8 MPa respectively.      Key Words: carbon fiber; structural concrete elements; mechanical performance; nondestructive trials.